"No pain, no gain": The experience of women using sterile water injections. Issue 2 (April 2017) - Lee, Nigel; Kildea, Sue; Stapleton, Helen
Abstract: Problem/ background: Sterile water injections (SWI) are gaining popularity amongst women and midwives for the relief of back pain in labour. However the brief but intense pain associated with the injection has been cited as a deterrent to use and may negatively affect the birth experience. Aim: To explore women's experiences of using sterile water injections as analgesia for back pain in labour. Design: A qualitative study, which generated data through individual semi-structured interviews with postnatal women. Data were analysed thematically. Setting: Two metropolitan maternity units in Queensland, Australia. Participants: Nine postnatal women who had participated in a randomised controlled trial investigating the use of sterile water injections for back pain in labour Findings: Three major themes were identified including sterile water injections as a non-pharmacological injection; balancing injection pain against expectations of pain relief; the analgesic effect of sterile water injections. Key conclusions: Women in this study largely viewed sterile water injections as an effective analgesia with few side effects. The pain associated with the injection of sterile water was weighed against the likelihood of rapid, effective pain relief. Women used the period of analgesia to support their objectives, be this a period of respite during the labour or to enhance the ability to focus on the birth experience. Information on SWI provided by health professionals should also balance realistic descriptions of the injection pain with prospect of analgesia.